Analisis Kualitas Layanan Dan Kinerja Organisasi Badan Kepegawaian Negara: Kajian Sistem Aplikasi Docudigital - Gunarto, Muji; Helpina, Helpina (Catholic University Musi Charitas, 2023)
Researchers around the globe have conducted studies on organizational performance till these days, but it is still interesting to investigate this topic. Technological developments encourage civil servants to improve their performance. This study aims to identify the influence of the Docudigital system and service qualities on the organizational performance of the civil servants of the National Civil Service Agency (NCSA) in Palembang. One hundred and eighty-five respondents from the NCSA Palembang working area participated in the survey of this study. The analysis technique was carried out using a structural equation model (SEM) approach through the LISREL program package. The results of the study show that the Docudigital application system quality has a positive impact on the service quality of NCSA Palembang. Furthermore, the service quality has a positive and significant effect on the organizational performance of NCSA Palembang. Moreover, the Docudigital application system has a positive and significant effect on the organizational performance of NCSA Palembang. In short, NCSA Palembang needs to enhance the service quality by improving the application system and prioritizing accuracy, speed, and convenience.